Utilization of sunflower marble waste nanocomposites for efficient removal of dyes from wastewater: synthesis, adsorption performance, and characterization - Saeed, Tayaba; Hanif, Muhammad Asif; Rashid, Umer; Anwar, Hafeez; Bhatti, Ijaz Ahmad; Alharthi, Fahad A.; Han, Jeehoon; Yoo, Jiyun (Springer Science and Business Media LLC, 2023)
Pollution of dye-contaminated wastewater is increasing rapidly due to the increase in industrialisation. This research was designed to investigate the potential of sunflower marble waste for the removal of dyes, reactive black 5 and NOVAC black WNN, from wastewater using an adsorption process because of its low cost, easy availability, and eco-friendly nature. Four different combinations (SM, SMP, SMS, and SMPS) of sunflower marble waste nanocomposites were prepared. Morphological characteristics of the adsorbent nanocomposites were investigated by SEM (scanning electron microscopy), and functional group arrangements were studied by FTIR (Fourier transform infrared spectroscopy). Different factors affecting adsorption such as initial dye concentration, adsorbent dosage, pH, time, and temperature were also studied. Of all the four adsorbents, sunflower marble treated with potassium ferricyanide (SMP) showed a maximum adsorption capacity of 198.3 mg/g and 124 mg/g for NOVAC black WNN dye and reactive black 5 dye, respectively. Among Freundlich, Langmuir, Harkin Jura, Dubinin Radushkevich isotherm, and Temkin isothermal models, Freundlich adsorption isotherm was the best fit for all the adsorbents based on its high R2 value. Kinetic models (pseudo-first order and pseudo-second order) were tested to identify the potential of the adsorption process which showed that both the dyes followed second-order kinetics at equilibrium because their R2 > 0.9 and q experimental and q calculated were close to each other. Life cycle assessment (LCA) for synthesizing 1 kg of nanocomposite showed that SMP had lower values over all six environmental impacts than the others.